1990
DOI: 10.1111/j.1399-3054.1990.tb04383.x
|View full text |Cite
|
Sign up to set email alerts
|

Boron is required for the stimulation of the ferricyanide‐induced proton release by auxins in suspension‐cultured cells of Daucus carota and Lycopersicon esculentum

Abstract: Boron deficiency reduces the ferricyanide‐induced net proton release of suspension‐cultured carrot (Daucus carota L.) and tomato (Lycopersicon esculentum Mill.) cells by more than 50%. This effect is reversed within 60 to 90 min by the addition of B. Vanadate (400 μM) completely suppresses the proton release, indicating an ATPasedriven process. The differences between B treatments do not appear when auxins are omitted from the experimental solution, but can be observed within less than 30 min after the additio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1991
1991
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Lots of studies have shown that supplemental boron stimulates proton pumping in plants, causes hyperpolarization of the membrane potential, and increases potassium uptake. Along with these findings, there have been reports of a boron-mediated increase in ferricyanide reduction 19 - 22 . There is also strong evidence that boron is involved in lignin biosynthesis and in cell wall cross-linking in plants 23 .…”
Section: Discussionmentioning
confidence: 68%
“…Lots of studies have shown that supplemental boron stimulates proton pumping in plants, causes hyperpolarization of the membrane potential, and increases potassium uptake. Along with these findings, there have been reports of a boron-mediated increase in ferricyanide reduction 19 - 22 . There is also strong evidence that boron is involved in lignin biosynthesis and in cell wall cross-linking in plants 23 .…”
Section: Discussionmentioning
confidence: 68%
“…Much evidence suggests that B also plays a role in the structure and function of the plant plasma membrane ( Loomis and Durst, 1992 ; Blevins and Lukaszewski, 1998 ). Within minutes, B deprivation inhibits P i and Rb + uptake ( Pollard et al ., 1977 ; Goldbach, 1985 ) and ferricyanide-induced H + release ( Goldbach et al ., 1990 ), suggesting that B does not act only by maintaining wall integrity. Withholding B also causes visible abnormalities at the wall–membrane interface and is likely to be involved in the organisation of transvacuolar cytoplasmic strands and/or to participate in wall–membrane attachment ( Hirsch and Torrey, 1980 ; Bassil et al ., 2004 ).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, in our experiments higher B concentrations in the culture medium (> 0.1 mM) exerted a negative effect on the plasma membrane properties of explants and thus decreased K + uptake. In addition, B might influence plant reactions to environmental stimuli by modifying their response to auxins (Goldbach et al 1990).…”
mentioning
confidence: 99%